2005
DOI: 10.1007/s10750-005-2213-y
|View full text |Cite
|
Sign up to set email alerts
|

Flow permanence and macroinvertebrate community diversity within groundwater dominated headwater streams and springs

Abstract: The response of aquatic macroinvertebrate communities to flow permanence within limestone springs and headwater streams was examined across the English Peak District. At the regional scale, macroinvertebrate communities of perennial and intermittent springs displayed significant differences in the number of taxa, macroinvertebrate community abundance, diversity indices (Shannon and Simpson indices) and the Berger-Parker dominance index at intermediate discharge. However, no significant difference was recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
55
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 16 publications
(12 reference statements)
1
55
1
2
Order By: Relevance
“…Even methods for sampling hyporheic fauna in temporary rivers need improvements. In both cases (floods or drought), the major challenge is to know if the benthic organisms stored in the hyporheic zone can return to the benthic layer (Wood et al, 2005). In short, is the hyporheic zone a refuge or a graveyard?…”
Section: Introductionmentioning
confidence: 99%
“…Even methods for sampling hyporheic fauna in temporary rivers need improvements. In both cases (floods or drought), the major challenge is to know if the benthic organisms stored in the hyporheic zone can return to the benthic layer (Wood et al, 2005). In short, is the hyporheic zone a refuge or a graveyard?…”
Section: Introductionmentioning
confidence: 99%
“…In the conclusion our 35 study revealed that further conservation strategies for the protection of the riparian springs along 36 large rivers would take into account ongoing climatic changes and the positive impact of the 37 anthropogenic transformation of river valleys. 58 On the other hand, some studies have shown that the water mite composition inhabiting 59 intermittent springs differs from those assemblages that inhabit perennial springs (Smith, Wood 60 & Gunn, 2003;Wood et al, 2005). To date, the influence of neither of these disturbance factors 61 on water mite assemblages in riparian springs along a lowland river has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Von Fumetti & Nagel (2012) 58 On the other hand, some studies have shown that the water mite composition inhabiting 59 intermittent springs differs from those assemblages that inhabit perennial springs (Smith, Wood 60 & Gunn, 2003;Wood et al, 2005). To date, the influence of neither of these disturbance factors 61 on water mite assemblages in riparian springs along a lowland river has been studied.…”
mentioning
confidence: 99%
“…However, in the identification of other environmental variables shaping spring faunal assemblages, opinions of researchers vary. Water discharge associated with spring stability (Erman & Erman 1995;Smith & Wood 2002;Wood et al 2005;Von Fumetti et al 2006;Von Fumetti & Nagel 2011), substratum properties (Hahn 2000;Ilmonen & Paasivirta 2005) or temperature associated with altitude (Ferrington 1998;Lencioni et al 2011) or latitude (Ilmonen et al 2009) have been identified as the most important in most studies. Of course, it is a matter of available environmental gradients and spatial scale and there are few studies acknowledging water chemistry might have a significant influence on spring assemblages (Erman & Erman 1995;Lencioni et al 2011).…”
Section: Introductionmentioning
confidence: 99%